K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

38-(-12)=5-x+12

38+12=5-x+12

38=5-x

5-x=38

x=5-38

x=-33

8 tháng 2 2017

38-(-12)  =5-x+12

38+12    =5-x+12

38          =5-x+12-12

38          =5-x

x            =5-38

x            =-33

Vậy x =-33

6 tháng 12 2021

a) x-12=-15
x=-15+12
x=-3
b) 123-5(x+4)=38
5(x+4)=123-38
5(x+4)=85
x+4=85:5=17
x=17-4
x=13

6 tháng 12 2021

\(a.x-12=-15\)                    \(b.123-5.\left(x+4\right)=38\)

\(x=\left(-15\right)+12\)                        \(5.\left(x+4\right)=123-38\)

\(x=-3\)                                      \(5.\left(x+4\right)=85\)           

                                                   \(x+4=85:5=17\)

                                                    \(x=17-4=13\)

7 tháng 8 2019

a ) − 1 2 ≤ x < 2 3 = > x = 0. b ) − 1 < x ≤ 1 = > x ∈ {0;1}

12 tháng 11 2018

Đáp án D

3 8 : x = - 1 2 x = 3 8 : - 1 2 x = - 2 . 8 3 x = - 3 4

1 tháng 6 2017

Đáp án D

3 8 : x = - 1 2 x = 3 8 : - 1 2 x = - 2 . 8 3 x = - 3 4

23 tháng 3 2022

B

23 tháng 3 2022

b

19 tháng 1 2020

a) \(13+x=12-x\) \(\Leftrightarrow x+x=12-13\)

\(\Leftrightarrow2x=-1\)\(\Leftrightarrow x=\frac{-1}{2}\)

Vậy \(x=\frac{-1}{2}\)

b) \(19-\left(x+5\right)=\left(x-2\right)-\left(-38\right)\)

\(\Leftrightarrow19-x-5=x-2+38\)\(\Leftrightarrow14-x=x+36\)

\(\Leftrightarrow x+x=14-36\)\(\Leftrightarrow2x=-22\)\(\Leftrightarrow x=-11\)

Vậy \(x=-11\)

      \(13+x=12-x\)

\(\Rightarrow13+x+x=12\)

\(\Rightarrow13+2x=12\)

\(\Rightarrow2x=12-13\)

\(\Rightarrow2x=-1\)

\(\Rightarrow x=-1\div2\)

\(\Rightarrow x=-0.5\)

a) \(-28-7|-3x+15|=-70\)

\(\Rightarrow7|-3x+15|=42\)

\(\Rightarrow|-3x+15|=6\)

\(\Rightarrow|3\left(5-x\right)|=6\)

\(\Rightarrow|3|.|5-x|=6\)

\(\Rightarrow3|5-x|=6\)

\(\Rightarrow|5-x|=2\)

\(\Rightarrow\orbr{\begin{cases}5-x=2\\5-x=-2\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=3\\x=7\end{cases}}\)

Vậy \(x\in\left\{3;7\right\}\)

b) \(|18-2|-x+5||=12\)

\(\Rightarrow\orbr{\begin{cases}18-2|-x+5|=12\\18-2|-x+5|=-12\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}2|5-x|=6\\2|5-x|=30\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}|5-x|=3\left(1\right)\\|5-x|=15\left(2\right)\end{cases}}\)

Từ \(\left(1\right):\Rightarrow\orbr{\begin{cases}5-x=3\\5-x=-3\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=2\\x=8\end{cases}}\)

Từ \(\left(2\right):\Rightarrow\orbr{\begin{cases}5-x=15\\5-x=-15\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=-10\\x=20\end{cases}}\)

Vậy \(x\in\left\{2;8;-10;20\right\}\)

c) \(12-2\left(-x+3\right)^2=-38\)

\(\Rightarrow2\left(3-x\right)^2=50\)

\(\Rightarrow\left(3-x\right)^2=100\)

\(\Rightarrow\orbr{\begin{cases}3-x=10\\3-x=-10\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=-7\\x=13\end{cases}}\)

Vậy \(x\in\left\{-7;13\right\}\)

d) \(-20+3\left(2x+1\right)^3=-101\)

\(\Rightarrow3\left(2x+1\right)^3=-81\)

\(\Rightarrow\left(2x+1\right)^3=-27\)

\(\Rightarrow2x+1=-3\)

\(\Rightarrow2x=-4\)

\(\Rightarrow x=-2\)

Vậy \(x=-2\)

27 tháng 2 2021

Trả lời:

a, -28 - 7| -3x + 15 | = -70

=> 7| -3x + 15 | = 42

=> | -3x + 15 | = 6

=> -3x + 15 = 6 hoặc -3x + 15 = -6

=>   -3x = -9                    -3x = -21

=>  x = 3                            x = 7

Vậy x = 3; x = 7

b, | 18 - 2 | -x + 5 || = 12

=> 18 - 2| -x + 5 | = 12 hoặc 18 -  2| -x + 5 | = -12

=> 2 | -x + 5 | = 6   hoặc    2 | -x + 5 | = 30

=> | -x + 5 | = 3    hoặc      | -x + 5 | = 15

=>  -x + 5 = 3 hoặc -x + 5 = -3 hoặc -x + 5 = 15 hoặc -x + 5 = -15

=>  x = 2                     x = 8                  x = -10               x = 20

Vậy x \(\in\){ 2; 8; -10; 20 }

c, 12 - 2.( -x + 3 )2 = -38

=> 2.( -x + 3 )2 = 50

=> ( -x + 3 )2 = 25

=> -x + 3 = 5 hoặc -x + 3 = -5

=>   x = -2                x = 8

Vậy x = -2; x = 8

d, -20 + 3.( 2x + 1 )3 = -101

=> 3.( 2x + 1)3 = -81

=> ( 2x + 1 )3 = -27

=> 2x + 1 = -3 

=> 2x = -4

=> x = -2

Vậy x = -2

=> x = 1